A relação das tendinopatias do manguito rotador com as atividades cotidianas: uma contribuição para o design ergonômico - Pereira, Diego Dalvan [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Movements and postures performed domestically with household activities can cause injury to the shoulders, including the rotator cuff tendinopathy (RCT). Interdisciplinarity is fundamental for prevention of RCT, which affect mainly women after the fourth decade of life, and are caused, among other factors, by activities that require elevation of the upper limbs. This cross-sectional study aimed to demonstrate the importance of ergonomic intervention in the prevention of RCT in our daily activities, performed in homes and possible parameters to assist the ergonomic design and/or redesign of products that may be contributing to te development of these disorders. For data analysis were used descriptive statistics as the mean, standard deviation (SD) and percentage rate (%). Methods of inferential statistics such as Fisher's exact test and the chi-square test for multiple comparisons were also applied. All statistical tests were used considering a significance level of 0.05. Participated in the first stage of the study 344 subjects, where 69.5% were female, age ranged from 18 to 83 years, and 49.4 of average age year. The majority of the sample (76,4%) was in the age group of 40 years old and higher. There was evidence of the association of pain symptoms in the shoulder with the variables: has woken up in pain, did not perform surgery and dominant right upper limb. Housework is performed by 74.1% (255), where only 13.4% (46) of those were male. From the inclusion criteria, 64 individuals were selected for the second stage of research, in which was conducted an ergonomic research in their homes. Based on partial results it is concluded that some upper limbs postures adopted for use on handling of utensils, mainly by women during household chores, including sleep posture, are inadequade from a biomechanical and ergonomic point of view, since this overexposes a high risk of RCT

Movimentos e posturas executados no âmbito doméstico, com afazeres domésticos, podem causar lesões nos ombros, entre elas, as tendinopatias do manguito rotador (TMR). Interdisciplinaridade é fundamental na prevenção das TMR, que acometem principalmente mulheres após a quarta década de vida, são causadas, entre outros fatores, por atividades que exigem elevações dos membros superiores. Este estudo transversal teve por objetivo demonstrar a importância da intervenção ergonômica na prevenção das TMR em atividades do nosso cotidiano, realizadas em ambientes domésticos e possíveis parâmetros que auxiliem o design e/ou redesign ergonômico de produtos que possam estar contribuindo para o surgimento dessas afecções. Para análise dos dados, foram utilizadas técnicas de estatística descritiva como a média, desvio padrão (SD) e a frequência percentual (%). Foram empregados ainda métodos de estatística inferencial como o teste exato de Fisher e o teste de Quiquadrado, para comparação múltipla. Todos os testes estatísticos foram utilizados considerando um nível de significância de 0.05. Participaram da primeira etapa deste estudo 344 indivíduos, sendo 69,5% do gênero feminino, a faixa etária variou entre 18 e 83 anos de idade, com média de 49,4 anos. Grande parte da amostra (76,4%) encontra-se na faixa etária acima dos 40 anos de idade. Houve evidências de associação dos sintomas álgicos no ombro com as variáveis: já acordou com dor, não realizou cirurgia e membro superior direito dominante. Afazeres domésticos são realizados por 74,1% (255), desses, apenas 13,4% (46) são do gênero masculino. A partir dos critérios de inclusão, foram selecionados 64 indivíduos para segunda etapa da pesquisa, onde se realizou uma investigação ergonômica nos respectivos ambientes domésticos. Com base nos resultados parciais conclui-se que algumas posturas dos membros superiores adotadas para o uso e manuseio de alguns...
The relationship of a rotator cuff tendinopathy with everyday activities: a contribution to the ergonomic design
Keywords: Engenharia humana; Desenho industrial; Fisioterapia; Ombro; Trabalho; Human engineering